2009
DOI: 10.1620/tjem.217.329
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological Conditions Related to the Onset of Spontaneous Pneumothorax

Abstract: Spontaneous pneumothorax is defined as the rupture of bleb or emphysematous bullae that develop just beneath the pulmonary pleura. Weather changes may influence the incidence of spontaneous pneumothorax. The aim of this study was to examine the influence of rainfall, temperature and atmospheric pressure changes on the onset of spontaneous pneumothorax. The study involved 669 spontaneous pneumothorax admissions to three reference hospitals in Ankara, Turkey between 1996 and 2006 (612 males and 57 females with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 15 publications
5
38
0
6
Order By: Relevance
“…It has been suggested that the undulation of the weather conditions cause weakening of the walls of small air cysts in lungs. However, we obtained results similar to some other trials that have reported no relationship between SP incidence and seasons, months [7]. SP occurs in episodes and clusters [11,12].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…It has been suggested that the undulation of the weather conditions cause weakening of the walls of small air cysts in lungs. However, we obtained results similar to some other trials that have reported no relationship between SP incidence and seasons, months [7]. SP occurs in episodes and clusters [11,12].…”
Section: Discussionsupporting
confidence: 89%
“…Incidence of pneumothorax is around 18-28/100.000 in men and 2-6/100.000 among women [3,7]. In our study, 92% of the patients were male and the rest were female.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…[7][8][9][10][11][12][13][14] There are 4 reports demonstrating positive relationship on the atmospheric pressure and the onset of pneumothorax. Bense et al reported a significant increase in the number of hospitalizations for SP within the 2-day period following a decrease of 10 hPa or more in the atmospheric pressure within a time-period of 24 hours.…”
Section: Discussionmentioning
confidence: 99%